Sistem Pertanian Masyarakat Wewengkon Adat Kesepuhan Citorek Tahun 1990-2021 - Nur Sahroniah; Eko Ribawati; Arif Permana Putra (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This study aims to determine the Community Agricultural System of Wewengkon Adat Kesepuhan Citorek in 1990–2021. This research method is the historical method, including; heuristic stage, source criticism, interpretation, and historiography. The research analysis uses the moral economic theory of farmers by Scott, the theory of rational farmers by Samuel L. Popkin and the theory of cultural value orientation by Kluckhohn. The results of this study show that the Citorek Kesepuhan Customary Wewengkon is located at an altitude of 500-1050 meters above sea level, a mountain which includes the Mount Halimun Salak National Park (TNGHS). There are two main rivers (Citorek River and Cimadur River) to support farming. The life of the Wewengkon Adat Kesepuhan Citorek community in 1990–2021 in implementing the agricultural system shows two characters, firstly the morale of the farmer's economy is subsistence by complying with various agricultural regulations or prohibitions (start of farming time, holidays farming, use of rice types, and tabernacles) secondly has the character of rational farmers who are open to the use of agricultural technology such as rice field plowing tools (tractors), rice grinding machines, fertilizers (urea and bungkil) and weed killer. Local traditions of the Wewengkon community's Wewengkon Adat Kesepuhan Citorek community traditions such as salametan, nabeh goong gede, ngarengkong and seren tahun have (1) cultural values, namely deliberation, religion and obedience (2) meanings, namely the relationship between humans and humans, nature, time, creation, and with himself. Keywords: Agricultural System, Wewengkon Adat, Kesepuhan Citorek.